1999
DOI: 10.1007/bf02513350
|View full text |Cite
|
Sign up to set email alerts
|

Combined wavelet transformation and radial basis neural networks for classifying life-threatening cardiac arrhythmias

Abstract: Automatic detection and classification of arrhythmias based on ECG signals are important to cardiac-disease diagnostics. The ability of the ECG classifier to identify arrhythmias accurately is based on the development of robust techniques for both feature extraction and classification. A classifier is developed based on using wavelet transforms for extracting features and then using a radial basis function neural network (RBFNN) to classify the arrhythmia. Six energy descriptors are derived from the wavelet co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(48 citation statements)
references
References 16 publications
0
48
0
Order By: Relevance
“…Take computerized ECG arrhythmia interpretation for an example. It has been confirmed that Hermite basis functions (HBFs) and wavelet energy descriptors are among those most competitive ones for feature characterization in discrimination analysis (Senhadii et al, 1995;Rasiah et al, 1997;AI-Farhoum & Howitt 1999;Lagerholm et al, 2000;Saxena et al, 2002;Linh et al, 2003;Engin 2007).…”
Section: Adaptive Physiological Signal Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Take computerized ECG arrhythmia interpretation for an example. It has been confirmed that Hermite basis functions (HBFs) and wavelet energy descriptors are among those most competitive ones for feature characterization in discrimination analysis (Senhadii et al, 1995;Rasiah et al, 1997;AI-Farhoum & Howitt 1999;Lagerholm et al, 2000;Saxena et al, 2002;Linh et al, 2003;Engin 2007).…”
Section: Adaptive Physiological Signal Modellingmentioning
confidence: 99%
“…Actually, signal representation in time domain is legible but redundant, which may be evidenced by means of PCA (Geva 1998;Stamkopoulos et al, 1998). As a consequence, morphological analysis was generally combined with domain transformation, such as Hilbert transform (Bolton & Westphal 1981), HD (Rasiah et al, 1997;Lagerholm et al, 2000;Linh et al, 2003) and WT (Senhadii et al, 1995;AI-Farhoum & Howitt 1999;Saxena et al, 2002;Engin 2007), in those published paradigms of computerized physiological signal interpretation. Domain transformation, unlike direct morphological analysis, attempts to characterize physiological signals in an alternative space, where the genuine signal components are more discernible from noises and artefacts.…”
Section: Adaptive Physiological Signal Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the time and frequency representation can be possible due the scaling property. It has made the wavelet transform suitable for analysis of the non-stationary signals such as speech and ECG signals [17][18][19][20]. This work is confined to ECG signal which remains noisy and non-stationary using the wavelet transform.…”
Section: Feature Extraction Using Wavelet Transformmentioning
confidence: 99%
“…Miiiami et al combined the feature extraction by Fourier transform and a back-propagation neural network (BPN) [4], and detected the tachyarrhythmia in real-time. Fahoum et al combined the WT and an R,BF neural network (R,BFN), in order to detect life-threatening cardiac arrhythmias [5]. The purpose of these reports was to detect the abnormal waveform on the ECG.…”
mentioning
confidence: 99%